GAMBARAN PENGGUNAAN ANALGETIKA PADA OPERASI ORTHOPEDI DI INSTALASI BEDAH SENTRAL RSUD dr. LOEKMONO HADI KUDUS - Maria Caecilia Nanny Setiawati; Hilda Wulan Suciati (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2021)
Orthopedic surgery is often performed, especially due to traffic accidents. Post orthopedic surgery, patients usually feel pain, thus requiring the administration of analgesics. The Objective of this research is to determine the characteristics of the patient and the description of the use of analgesic drugs, as well as the cost of drugs use in orthopedic surgery at the Central Surgical Installation of RSUD dr. Loekmono Hadi Kudus. This research is descriptive and the data are taken retrospectively. Sampling by purposive sampling method. In the period September-October 2019 there were 101 inpatients who underwent orthopedic surgery and received analgesics. 60.6% were male patients, 63.36% were BPJS users, the most age was between 36-45 years (19.80%), the most pain experienced by patients was moderate pain (69.31%). ). Most of the analgesics used were a combination of ketorolac injection and tramadol injection, as many as 48 patients (47.52%). The method of drug administration was mostly done intravenously (95.22%). The average cost of all drugs for orthopedic surgery is IDR 278,039, with analgesic drug costs as much as 14.4% of the total drug cost . The Conclusion is the most were BPJS patients, male, age between 36-45 years, the most analgesic use was combination tramadol and ketorolac, the use of analgesics and drug costs in orthopedic surgery is quite rational.